Edukasi dan Sosialisasi Kesehatan Lansia Pasca Pandemi COVID di Kemuning Lor Jember - Irma Harlianingtyas; Devi Arine Kusumawardani; Ramadhan Taufika; Dian Hartatie; Supriyadi (Puslitbang Sinergis Asa Professional, 2022)
COVID-19 causes an increase in morbidity and mortality until 2021. One of the important components in dealing with the threat of the Covid-19 pandemic is care for the elderly group. Jember Regency as one of the districts that experienced an increase in the percentage of the elderly from 2018 to 2020 requires special attention regarding the prevention of COVID-19 transmission in the elderly. Based on the survey results to service partners, several problems that need to be resolved are the lack of knowledge about increasing immunity, especially among the elderly, partners still do not have awareness about the dangers of the COVID-19 virus, partners have not implemented health protocols such as social distancing, washing hands regularly, wearing masks when leaving the house, and spraying disinfectants regularly. The solution provided by the proposing team is the service team providing education about the importance of healthy living and to increase awareness while adhering to health protocols during the pandemic. This activity was attended enthusiastically by the participants. this can be measured by 100% of the invitees attending the event. The education and socialization running smoothly. Communities are equipped with the knowledge and skills to make hand sanitizer independently. After this activity, the community is motivated to maintain health and comply with health protocols.